Determinants of bank efficiency: the portuguese case - Vilaça, Eduardo (2019)
The objective of this study is to evaluate the technical efficiency of the Portuguese banking sector in the most recent period and to identify the determinants that explain it. Methods: The methodology used consisted on the application of the non-parametric approach, Data Envelopment Analysis (DEA), to estimate the technical efficiency of the banks, in the period between the first semester of 2005 and the first semester of 2017. The analysis used the classic models CCR and BCC following the banking intermediation approach. Findings & Value added: The results, in general, indicate that the level of efficiency of the Portuguese banking sector is high, suggesting that the banks operating in it are efficient in optimizing their resources. It also concludes that the determinants that influence efficiency are the size, the capital structure, the antiquity and the macroeconomic situation of the country. To the best of our knowledge, this is the first approach to bank efficiency that involves time series data after the Portuguese sovereign debt crisis and, therefore, were not considered in previous studies.